Development of bioclogging methods for soils - Tan, Wendy Zhaorong. (2011)
Presently, Chemical Grouting has been used to reduce the hydraulic conductivity and increase the strength of soil. However, chemical grouting is expensive and pollutes the environment to a certain degree due to toxic materials being injected into the soil. Hence, there is a need to look into biological stabilization. Biclogging is a type of biological stabilization that reduces the porosity and hydraulic conductivity of soil without polluting the environment. It is done by allowing the bacteria to grow and release enzyme thus triggering reactions to produce products to fill the pores of the soil. For example, in the presence of urea and calcium chloride (medium), urease-producing bacteria (UPB) would produce the enzyme urease and hydrolyzes it to ammonium chloride and calcium carbonate which are the microbial products.